A Systematic Review and Meta-Analyses of Nonsucrose Sweet Solutions for Pain Relief in Neonates - Mariana Bueno; Janet Yamada; Denise Harrison; Sobia Khan; Arne Ohlsson; Thomasin Adams-Webber; Joseph Beyene; Bonnie Stevens (Pain Research and Management)
BACKGROUND: Sucrose has been demonstrated to provide analgesia for minor painful procedures in infants. However, results of trials investigating other sweet solutions for neonatal pain relief have not yet been synthesized.